Csokonai Csókjai: Egy szöveg formálódásának tanulságai - Fülöp, Dorottya (Studia Litteraria, 2024)
Csokonai’s A’ Tsókok ("The Kisses") is a love epic in prose that borrows from the world of pastoral drama and was originally intended to comprise twelve cantos. It remained unfinished but is nevertheless often considered the greatest accomplishment of Csokonai’s early literary career. Csokonai borrowed liberally from his earlier readings and translation attempts during the creation of the text, and literary historiography has already made a detailed accounting of the exact locations and sources of such transplants. This study uses close textual analysis to reveal the sensitive poetical solutions employed by Csokonai to uncover parts where he inventively deviated from the patterns followed, and to point out the carefully structured network of motifs present in the finished parts.